Energy efficiency evaluation in a commercial building by strategic auditing and demand side management - Brar, Gagandeep Singh (My University, 2019)
In the ever-growing demand scenario, energy efficiency in the commercial and residential buildings has gained momentum in the recent years. At distribution level, the important function of energy management system are considered as, 1. Strategic Energy Auditing (EA) 2. Demand Side Management (DSM) Energy auditing (EA) is the cost effective means to identify the requirements of power components and their operation. This is due to the fact that in a commercial and residential building the major components are lighting source and heating, ventilating and air conditioning. The number of these components, to be installed, depends upon the area covered and the operating requirements like minimum lumens, air circulation in cubic feet per minute and the temperature level. In this scenario, EA allows identifying the methods, scope and time for energy management and helps the costumers to manage their energy consumption wisely in order to reduce their energy bills. In addition, the reduction in energy consumption reduces the carbon emission level and it leads to increase in sustainability of smart grid. However, most of the traditional strategies employ specific system techniques & algorithms whereas in recent years load shifting based DSM techniques have been used for the futuristic smart grid applications. In the commercial and residential buildings, the power consumption mainly depends upon the number of persons involved, surrounding temperature & humidity and the luminous intensity due to sun light. Considering the above fact, this work represents the review of different DSM techniques and the methodologies to achieve the desired objective of cost minimization under different operating scenario. The energy data of three month, in a year, is collected under three different seasonal changes i.e. January (severe cold), April (moderate) and August (severe hot). This gives a clear picture of variation in load demand under moderate, comfort and severe environmental conditions. The energy data under these three conditions are averaged and the DSM schemes are developed for the operation of power components before energy auditing and after energy auditing. Moreover, the performance of the proposed DSM techniques is compared with the practical results in both scenario and from the results it has been observed that the energy consumption has reduced significantly, in the proposed DSM approach.
Keywords: Energy efficiency, strategic auditing, commercial building, Demand side management, Algorithm